MiR-130c-5p targets the SHVV n gene and upregulates immune cytokines (IL-6, IL-22, IL-1β) to inhibit viral replication - Wei, Jin; Ji, Yan; Bai, Yaqian; Cheng, Rui; Zhang, Jiaqi; Hu, Xianqin; Zhang, Chi (Frontiers in Immunology, 2024)
Background Snakehead vesiculovirus (SHVV) has led to huge economic losses in snakehead aquaculture, and its pathogenic mechanisms is still not fully understood. MicroRNAs (miRNAs), as an important class of non-coding RNAs, play a key regulatory role in the process of viral infection. Methods We examined the effect of SHVV infection on the expression of miR-130c-5p and the effect of overexpression of miR-130c-5p on the proliferation of SHVV. Cotransfection of viral N protein and miR-130c-5p, and the effect of miR-130c-5p on the expression of N protein was detected. Meanwhile, the effect of overexpression of miR-130c-5p on the expression of various immune factors in the case of viral infection were also tested. Results In this study, SHVV infection significantly upregulated the expression of miR-130c-5p in channel catfish ovary (CCO) cells in a time- and dose-dependent manner. The further research revealed that miR-130c-5p mimic significantly inhibited, while its inhibitors promoted SHVV replication. In addition, miR-130c-5p could directly target the viral mRNA of n gene, and overexpression of miR-130c-5p could significantly decrease, and conversely, downregulation of miR-130c-5p could increase the mRNA and protein expression of the viral n gene. Meanwhile, overexpression of miR-130c-5p also upregulated the expression of immune-related genes, such as nucleotide-oligomerization domain (NOD)-like receptor subfamily C3 (NLRC3), myeloid differentiation factor 88 (MyD88), nuclear factor kappa-B (NF-κB), interleukin-6 (IL-6), interleukin-22 (IL-22), and interleukin-1beta (IL-1β) in host cells. Conclusion miR-130c-5p was upregulated in the host during SHVV infection, and the upregulated miR-130c-5p directly inhibited viral replication by targeting the n gene of SHVV and promoting viral nucleoprotein degradation. The up-regulated miR-130c-5p also activated the expression of immune-related genes such as NLRC3, MyD88, NF-κB, IL-6, IL-22, and IL-1β, which were involved in the regulation of the signaling pathways including NF-κB, MyD88, Toll-like receptor (TLR), NLR, and janus tyrosine kinase-signal converter and activator of transcription (JAK-STAT), to enhance the host's antiviral immune response, and thus indirectly inhibited the viral proliferation.